An archive of data from resonant column and cyclic torsional shear tests performed on Italian clays. Issue 1 (February 2021) - Facciorusso, Johann
Measurement of soil properties under cyclic and dynamic loading conditions is a critical task in the solution of most geotechnical earthquake engineering problems. The main dynamic properties of soils are usually expressed in terms of shear modulus, G, and damping ratio, D, and they are generally obtained from laboratory tests at different strain levels. Dynamic geotechnical problems often require a site-level or territorial approach involving a considerable number of dynamic laboratory tests that might be too expensive and time-consuming. Thus, it is a common practice to use empirical relationships between dynamic parameters and measurements from routine geotechnical tests. Therefore, the availability of a large and reliable archive of multiple testing results constitutes a fundamental step for geotechnical earthquake engineers and researchers. To this aim, a large data-set of the index and dynamic parameters measured from 170 undisturbed clay samples obtained from 90 sites in Central and Northern Italy is made available, and its use and application are further described and discussed.